2009
DOI: 10.5483/bmbrep.2009.42.10.661
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of porcine pancreas development

Abstract: Porcine pancreas development is not well studied at the molecular level despite being a therapeutic resource for diabetic patients. In this study, we investigated expression of lineage markers and performed proteomic analysis. Expression of the early lineage markers Pdx1 and Ptf1a was developmentally conserved between mice and pigs, whereas expression of the islet differentiation marker Pax4 was delayed in porcine compared with murine pancreas development. Proteomic analysis found that expression levels of chy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“… Do et al (2014b) reported that insulin signaling pathway plays important roles in controlling RFI in Duroc pigs, and it has been shown that insulin also affects feed intake and feed behavior in chickens ( Shiraishi et al, 2008 , 2011 ). Moreover, many reports showed that PDX1 was closely related to porcine pancreas development ( Choi et al, 2009 ) and diabetes ( Matsunari et al, 2014 ). Pancreas and diabetes are closely related to feed intake, digestion, absorption, and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“… Do et al (2014b) reported that insulin signaling pathway plays important roles in controlling RFI in Duroc pigs, and it has been shown that insulin also affects feed intake and feed behavior in chickens ( Shiraishi et al, 2008 , 2011 ). Moreover, many reports showed that PDX1 was closely related to porcine pancreas development ( Choi et al, 2009 ) and diabetes ( Matsunari et al, 2014 ). Pancreas and diabetes are closely related to feed intake, digestion, absorption, and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Clusters of orthologous groups of proteins were categorized and constructed using the NCBI genome database [3]. Relative protein abundance based on the emPAI from CO-metabolizing hydrogenase clusters was performed using Excel 2007 and DAnTE v1.0, both R-based bioinformatics tools, as described previously [18].…”
Section: Protein Identification and Semi-quantificationmentioning
confidence: 99%
“…In porcine pancreas, PFDN presents a differential expression according to the stage of the development, being downregulated after birth, following similar expression patterns as other cytoskeletal regulatory proteins ( Choi et al., 2009 ). Surprisingly, auto-antibodies against PFDN2 were found significantly enriched in type 2 diabetes patients, especially in those with an early onset of the disease ( Chang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%